STATUS GIZI STUNTING TERHADAP TINGKAT PERKEMBANGAN ANAK USIA BALITA - Yena Wineini Migang (Universitas Pahlawan, 2021)
The problem of stunting is the main program that gets priority intervention because it is associated with the risk of morbidity and mortality, one of which is stunted brain development. Children under fives will experience developmental delays, which will affect the productive age. Data from the Indonesian Ministry of Health, Directorate General of Public Health, Directorate of Nutrition, Central Kalimantan in 2015 the percentage of stunting aged 0-59 months was (38.4%), 2016 (34.1%) and 2017 (39.0%) in 2018 (34%) ). The 2020-2024 RPJM targets 19% and Central Kalimantan targets the next 4 years of 20% of the incidence of stunting and was issued by Governor Regulation No.13 of 2019 concerning actions to accelerate the prevention of stunting in 2019-2023. The research objective was to see the difference in the proportion of children under five development in the stunting nutritional status group of children children under five with normal nutrition. The research was carried out in Sebangau Subdistrict, Pulang Pisau Regency in 2019. The number of respondents was 30 groups of children children under five with stunting and 30 normal children children under five, with a case control study, purposive sampling technique, and Chi Square statistical test and Fisher Exact Test and binomial alternatives. There is a significant difference in the proportion of underfives' nutritional status with under-five development 0.000